Self-reported halitosis and associated demographic and behavioral factors - Fernanda Carpes MILANESI; Bruno KAUER; Tassiane Panta WAGNER; Luciana Dondonis DAUDT; Alex Nogueira HAAS
Abstract Halitosis is still poorly studied in young adults. The aim of this study was to evaluate the occurrence of self-reported halitosis and associate it with demographic and behavioral factors in young adult dental students. This cross-sectional study was designed as a census of students enrolled in three initial and three final semesters of a dental course in a Brazilian public university. Of 284 eligible students, 257 (90.5%) completed a self-administered questionnaire. Self-reported halitosis was the primary study outcome, and was assessed with the question "do you feel you have bad breath?". Data on age, gender, frequency of tooth brushing and interproximal cleaning, tongue cleaning, mouth rinse use and dry mouth were collected using the questionnaire, and were considered independent variables. Of the students surveyed, 26.5% reported as never, 51.7% as rarely, 21.4% as sometimes, and 0.4% as always feeling they had halitosis. Morning halitosis was reported by 90.6% of those who reported halitosis. In the final multiple model, last semester students had a 55% lower chance of reporting halitosis, compared with students from the first semesters [odds ratio (OR) 0.46; 95%CI 0.24-0.89]. Women had a 2.57fold higher chance of reporting halitosis (OR = 2.57; 95%CI 1.12-5.93). Dry mouth increased the chance of self-reported halitosis 3.95-fold, compared with absence of dry mouth (OR = 3.95; 95%CI 2.03-7.68). It can be concluded that self-reports of halitosis were low among dental students, but may represent an important complaint. Gender, dry mouth and level of college education of the dentist were factors significantly associated with self-reported halitosis.